GCA_blueberry_Frontiers2020.xlsx - Falagán, Natalia; Terry, Leon A.; Miclo, Tiana (Cranfield University, 2020)
Underlying data for the paper:Falagan N, Miclo T and Terry LA (2020) Graduated Controlled Atmosphere: A Novel Approach to Increase Duke Blueberry Storage Life. Front. Plant Sci. 11:221. doi: 10.3389/fpls.2020.00221
Keywords: Vaccinium corymbosum L.'; 'postharvest'; 'quality'; 'cold storage'; 'controlled atmosphere'; 'Packaging; Storage and Transportation (excl. Food and Agricultural Products)'; 'Food Engineering'; 'Food Packaging; Preservation and Safety'